Sustainable practices: the production of concrete aggregates from recycled sources / Amir Khomeiny Ruslan ... [et al.] - Ruslan, Amir Khomeiny; Md Nor, Noorsuhada; Mat Saliah, Soffian Noor; Md Hasan, Ahmad Syauqi; Jamaludin, Amril Hadri; Fauzi, Mohd Azrizal (Unit Penerbitan FKAPP, 2022)
On March 1st to March 22nd, 2023, an activity to produce recycled fine aggregate (RCA) was conducted involving 21 students under the supervision of 6 lecturers. The aim of this activity was to produce recycled fine aggregate for wall panel construction and material testing. To conduct this test, a total of 3000 kg of RCA needed to be prepared. This was not an easy task, but with the help of many students and the use of a highly efficient jaw crusher, the work was successfully completed in just 7 days. To produce RCA, test cubes were taken from the concrete mixing site. A total of 540 cubes were required to produce 3000 kg of fine RCA. With an average weight of 8 kg per cube, only 5.5 kg of fine RCA was successfully sieved out. On average, each concrete cube would produce approximately 70% of RCA passing through the 5 mm sieve, with the remaining retained at 5 mm. The construction industry is constantly seeking ways to improve sustainability and reduce the impact of its activities on the environment. In this regard, recycling concrete to produce aggregates has emerged as a promising solution. The process to produce recycled concrete aggregate involves three main stages. The first stage is known as, split and break, involves splitting and breaking the concrete into manageable sizes. A hacking tool is used to split the concrete, followed by using a hammer to break it down into chunks of 5cm x 5cm. This stage is crucial in ensuring that the concrete is of the right size for further processing.